Bali is Dressing-Up: Ritual as an Identity - RAKA, Anak Agung Gede; ANOEGRAJEKTI, Novi; YASA, Putu Ngurah Suyatna; MACARYUS, Sudartomo; GUNAWARMAN, Anak Agung Gede Raka (Journal of Environmental Management and Tourism; Vol 11 No 6 (2020): JEMT Volume XI, Issue 6(46) Fall 2020DO - 10.14505/jemt.v11.6(46).26, 2020)
Barong Landung in Bangli is recognized as one of the former relics of Bali-China contact. This visibly appears from character of its face and narrow lines of eyes. The contact between Balinese and Chinese culture is intertwined through trade channels. With an ethnographic method, the provision of library data of the present study was complemented by field data collected through observation, participation, and in-depth interview with selected participants. Interpretation was done semiotic, by placing each data as a phenomenon of interconnected culture as a whole. The results showed that Sacred Barong Landung was purified and stored in the temple and used in ritual activities that took place inside and outside the temple, such as walking around the village where the temple is located. Sacred Barong Landung is located at Pura Pusering Jagat, Pejeng, Gianyar and at Penataran Sima Siladan Temple, Taman Bali. Profane Barong Landung is situated in Gurukula Foundation, Kubu Sub-district, Bangli and in Sukawati, Gianyar. Traditional theater Calonarang play as a ritual brought in audiences from all levels of the society, including children, teenagers and elderly. Every person coming into the temple follows the activity until the end at the early hours. All the activities are a series of procession of religious activities as a form of benediction to God and as a medium to plead with Him to enable the whole community to always be in a harmonious state in the future.